Multiscale modelling: hybrid quantum mechanics/molecular mechanics as an example and some recent developments - Ghosh, Debashree (Current Science, 2017)
Most of the physical phenomena are multiscale in nature and therefore, to depict it properly one requires multiscale modelling techniques, i.e. physical models that are accurate over multiple length and time scales. The seminal work by Warshel and Levitt marks the beginning of hybrid quantum mechanics/molecular mechanics (QM/MM) method as a successful strategy towards the understanding of chemistry and physics in condensed phases and especially in biological systems. Recently, these methods have been extended to problems such as light-matter interaction, where the QM sub-system is excited from the ground to the excited states. The MM environment provides a field that changes the potential energy landscape of both the ground and excited states in a distinctly different way. In this review, we discuss the general strategy of multiscale modelling with emphasis on hybrid QM/MM and the recent developments in excited state QM/MM methods.